APPLICATIONS OF THE HELLENIC NATURAL ZEOLITE (HENAZE) AND SPECIFICATIONS OF ZEOLITIC TUFFS - Filippidis, A. (Bulletin of the Geological Society of Greece, 2016)
The Hellenic Natural Zeolite (HENAZE) is free of fibres and contains 89 wt% clinoptilolite, 3 wt% mica + clay minerals, 3 wt% quartz, 2 wt% cristobalie ± tridymite and 3 wt% feldspars. HENAZE do not meet the requirements of the EU Regulation No 651/2013, and thus cannot be used as feed additive for all animal species and consequently as nutrition supplement, since it contains 3 wt% quartz. HENAZE is suitable for use as soil conditioner, since the concentration of trace elements are lower than the maximum allowable concentrations in agricultural soils (EU Directive 278/1986). HENAZE as soil conditioner: a) improved the pH of acid soils by 47-55%, b) reduced the leaching of metals by 33-71% from contaminated soils, c) reduced the Hg concentration by 47-78% in shoots and roots of plants, d) increased the production of agricultural products by 17-95%, e) decreased the plantlosses in new vineyard by 12% and f) improved the quality of tomato by 4-46%. The HENAZE neutralized sewage sludge (producing zeo-sewage-sludge), industrialsludge (producing zeo-sludge), battery solid waste and mine solid wastes (minetailings). The zeo-sewage sludge and zeo-sludge are odorless, cohesive and suitable for safe deposition. The treatment of sewage-sludge and industrial-sludge with the HENAZE, reduced the leaching of metals by 91-100% and of NO3 - by 81-82%. Depending on the trace element contents, the zeo-sewage-sludge can be used as soil conditioner. HENAZE sorbed-removed 37-92% of metals, radionuclides and cyanobacteria from their solutions and waters. The treatment of wastewaters (urban, dyeing-industry, industrial area and tanning-work) with HENAZE, improved the quality characteristics by 48-99%. The HENAZE reduced the NO3 - load by 54-94% in groundwater, nitrate-solutions, industrial and urban wastewaters. Considering, the European, Global and Greek legislation, the mineralogical, chemical, morphological and radiological characteristics, as well as the leachability and bioavailability of chemical elements, the specifications for the different applications-uses of the zeolitic tuffs are defined